Membangun Ekonomi Kreatif Syariah Dari Lingkungan Masjid - Mokhlas; Yusqi Mahfud (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
Mosques do not only function as places of worship, but also have great potential as centers for the economic empowerment of the community. This service discusses the strategic role of mosques in building a creative economy based on Sharia values. Sharia creative economy prioritizes innovation, halal compliance, and blessings in the production and distribution processes of goods and services. The mosque environment, rich in values of brotherhood and collective spirit, becomes an ideal ecosystem for fostering community-based economic activities, such as sharia cooperatives, halal entrepreneurship training, and sharia MSME product bazaars. This service uses a qualitative approach with case studies in several active mosques in Central Java, but more specifically on the administrators, congregants, and the community around the Baiturrahman Gendong Grand Mosque RT. 05 RW. 05 Mangunharjo Tembalang, Semarang City. The study results show that the synergy between mosque management, the community, and Islamic financial institutions can create an inclusive and sustainable microeconomic system. By harnessing the potential of mosques, Muslims can build economic independence that not only has financial impacts but also spiritual and social ones.